Luteolin Suppresses Endothelial Permeability and Nitric Oxide Scavenging Effects - Yoong, Wong Theen; Choong, Shuit Siew; Fauzee, Mohd Sofian Omar; Ahmad, Zuraini; Hakim, Muhammad Nazrul (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Numerous inflammatory diseases are linked to increased endothelial permeability through the nitric oxide (NO) flux in endothelial cells. Luteolin has in vitro and in vivo anti-inflammatory properties and has been reported to reduce endothelial permeability. However, the exact mechanism/s are yet to be determined. Thus, the present study was conducted to investigate the effects of luteolin in reducing endothelial permeability in vitro using bradykinin (BK) or sodium nitroprusside (SNP) through the NO pathway and the NO radical scavenging property of luteolin.METHODS: Human umbilical vein endothelial cells (HUVECs) in the treatment groups were dosed with luteolin at 5, 10, and 25 µM concentrations and allowed to incubate for one hour prior to induction. The L-NAME or HOE 140 were administered prior to the induction of BK or SNP in HUVECs. The NO radical scavenging test, the nitrite determination assay using L-NAME as antagonist, and the in vitro vascular permeability testing using HOE 140 as antagonist were performed.RESULTS: Endothelial permeability was decreased dose-dependently by 5, 10, and 25 µM luteolin in vitro via lowering NO generation. In comparison to HOE 140, luteolin suppressed the enhanced endothelial permeability more effectively. The suppression was 98.02% by 25 µM luteolin compared to HOE 140 94.05%. It was also discovered that luteolin, when incubated with SNP in a dose-dependent manner, possessed potent NO radical scavenging activities.CONCLUSION: The current data demonstrated luteolin's ability to scavenge NO radicals and significantly decrease endothelial permeability through the NO route. Thus, in complementary medicine, luteolin might be potential to improve endothelial permeability suppressor in reducing inflammation.KEYWORDS: luteolin, endothelial permeability, NO, scavenging property, HUVECs